2021
DOI: 10.1038/s41380-021-01306-8
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and depression in young people: a systematic review and proposed inflammatory pathways

Abstract: Depression onset peaks during adolescence and young adulthood. Current treatments are only moderately effective, driving the search for novel pathophysiological mechanisms underlying youth depression. Inflammatory dysregulation has been shown in adults with depression, however, less is known about inflammation in youth depression. This systematic review identified 109 studies examining the association between inflammation and youth depression and showed subtle evidence for inflammatory dysregulation in youth d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 195 publications
(223 reference statements)
1
37
2
Order By: Relevance
“…Some studies have documented an association between inflammation and depression and reported that higher concentrations of pro-inflammatory cytokines possibly directly contribute to the development of depressive symptoms (11,82,83). The current study found that the serum IL-6 level was positively associated with depression; however, this association was not significant after controlling for the age effect.…”
Section: Depression and Irritabilitycontrasting
confidence: 80%
“…Some studies have documented an association between inflammation and depression and reported that higher concentrations of pro-inflammatory cytokines possibly directly contribute to the development of depressive symptoms (11,82,83). The current study found that the serum IL-6 level was positively associated with depression; however, this association was not significant after controlling for the age effect.…”
Section: Depression and Irritabilitycontrasting
confidence: 80%
“…In this analysis, peripheral cytokine levels were observed to be elevated in pediatric internalizing disorders compared to controls. A recent meta-analysis by Toenders et al (2022) reported a significant elevation of peripheral IL-1β levels in youth depression ( k = 7, Cohen's d = 0.37) that was not observed in our moderator analysis. However, we acknowledge the differences in our statistical approach (univariate versus multi-variate), larger sample sizes in our IL-1β moderator analysis, and our mixed sample of anxiety and depression as potential reasons for the deviation when comparing our findings.…”
Section: Discussioncontrasting
confidence: 69%
“…Data from this study was converted to an estimated mean and standard deviation using a precise, low bias statistical method under the assumption of a skewed raw dataset ( Wan et al, 2014 ; Weir et al, 2018 ). A quality assessment of the studies included in the systematic review was performed and based on the criteria developed by Toenders et al (2022) utilizing the Cochrane Consumers and Communication Review Group Study Quality Guide (2013) and the Critical Appraisal Skills Programme (CASP) ( Ryan et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations